Kompetensi Pedagogik Guru Dalam Mengelola Interaksi Kelas Pada Pembelajaran Bahasa Indonesia Sekolah Dasar - Jafarudin Jafarudin (Jurnal Sultra Elementary School, 2022)
This research was conducted in Grade 6 at SD Negeri 1 Barangka from April to May 2022. The study aimed to describe the teacher’s pedagogical competence in classroom management during the learning process—specifically in opening, presenting, and closing Indonesian language lessons. Data were collected through observation and interviews. The results of this descriptive study indicate that the teacher’s competence in opening the lesson was of good quality, the competence in presenting the material was of very good quality, and the competence in closing the lesson was of less satisfactory quality. The conclusion of this study shows that the overall quality of the teacher’s competence in managing classroom interaction during Indonesian language learning in Grade 6 at SD Negeri 1 Barangka achieved a good level in the aspects studied.